1997
DOI: 10.1055/s-2007-979052
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Free Radical Scavengers and Lipid Peroxide in Thyroid Glands of Various Thyroid Disorders

Abstract: To clarify whether the changes of free radicals and its scavengers are induced by thyroid disorders, we measured levels of free radical scavengers and checked °2 radical generating systems in the human thyroid gland.Thyroid specimens from patients with Graves' disease, follicular adenoma, and papillary and follicular carcinomas contained significantly higher concentrations of xanthine oxidase (XOD) and gluthathione peroxidase (GSH-PX), compared to those in the normal thyroid tissue. Catalase concentration was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 5 publications
1
25
0
4
Order By: Relevance
“…Plasma MDA levels with hyperthyroidism prior to treatment to be significantly higher than control group, with the levels decreasing after treatment [20]. Consistent with other studies [21,22], in our study MDA levels were higher in patients with hyperthyroidisms compared to control group ( heart, hepatic and brain tissue [23,24]. It is known that lipid peroxidation and generation of ROS leads to oxidative stress and damage.…”
Section: Resultssupporting
confidence: 90%
“…Plasma MDA levels with hyperthyroidism prior to treatment to be significantly higher than control group, with the levels decreasing after treatment [20]. Consistent with other studies [21,22], in our study MDA levels were higher in patients with hyperthyroidisms compared to control group ( heart, hepatic and brain tissue [23,24]. It is known that lipid peroxidation and generation of ROS leads to oxidative stress and damage.…”
Section: Resultssupporting
confidence: 90%
“…Decreases in CAT activities were found in brown adipose tissue after T3 or T4 treatment [130] and in liver [11,16], whereas lack of change [120,156,179] and decrease [11] were found in heart.…”
Section: Antioxidant Statusmentioning
confidence: 93%
“…Indeed, it was reported that cardiac activity decreased after longterm T4 treatment of both young [11,156] and old [120] rats, increased [118] and remained unchanged [120] after long-term T4 treatment of young rats, and remained unchanged after short-term T3 treatment of young rats [110]. Liver GPX activity was found to decrease after T4 treatment [11], but both increased [16] and remain unchanged [110,199] after T3 treatment.…”
Section: Antioxidant Statusmentioning
confidence: 95%
See 1 more Smart Citation
“…When ROS are produced in higher amounts, they are systematically eliminated by potent antioxidant systems such as peroxiredoxins, catalase, and glutathione peroxidases. [1][2][3][4][5] Thus, a basal ROS production, which we define as oxidative load, is required to safeguard thyroid hormone synthesis, as recently demonstrated. 6 Likewise, an harmless oxidative stress (OS) may also be important for cell division during goiter formation when thyrocytes are facing iodine deprivation.…”
mentioning
confidence: 89%